0131 Changes in the Composition and Mechanical Properties of the Tongue Following Weight Gain in Zucker Rats. (27th April 2018) - Brake, L A; Lin, T C; Hoge, C; Keenan, B T; Loro, E; Azad, N; Nguyen, T; Wiemken, A S; Mellia, J A; Schwab, R J
Abstract: Introduction: Although the mechanisms through which obesity contributes to obstructive sleep apnea (OSA) are unknown, OSA patients have increased tongue fat compared to controls. Animal models can be used to study the effect of weight gain on tongue fat. We studied obese (OBZ) and lean (NBZ) Zucker rats longitudinally (3 months), and hypothesized: (1) the amount of tongue fat would increase in both OBZ and NBZ rats following weight gain; and (2) mechanical properties of the tongue would be adversely affected because of fat deposition. Methods: A subset of 12 NBZ and 12 OBZ males were euthanized monthly to identify longitudinal changes in tongue force and composition. Spin-echo and Dixon MRI were used to obtain the total and fat volumes of the tongue and masseter at baseline and monthly. Tongue force values were obtained by stimulating the hypoglossal nerves of anesthetized animals. Results: Tongue volume, fat volume and fat percentage increased longitudinally in both groups (p<0001). There was no change in masseter fat percentage despite the volume of this muscle increasing (p<0.001). Changes in tongue volume and fat measures were similar between groups. Among all rats, there were significant positive associations between weight and tongue volume, tongue fat volume, and tongue fat percentage (p<0.0001). There were no significant associations between weight gain and tongue force outcome variables. Conclusion: Tongue volume, tongue fat volume, and tongue fat percentage were positively associated with weight gain in OBZ and NBZ rats. Fat preferentially deposited in the tongue compared to the masseter. Increased tongue fat may contribute to the relationship between obesity and OSA. There were no significant associations between weight and tongue force measures. Rats had baseline tongue fat percentages averaging 2.6% compared to 27–33% seen in humans. It is possible the absolute amount of tongue fat in these animals was insufficient to produce significant changes in tongue force output. Future studies should consider examining weight gain in other animal models (pig/cow) with tongue fat percentages similar to humans. Support (If Any): Supported by NIH P01 HL094307.